A survey of key issues of URLLC in industrial internet of things - Han WANG; Lei DIAO; Mengling WANG; Xin RONG; Jiamin LI; Xiaohu YOU (Dianxin kexue)
In the age of 6G internet of things, massive terminal devices are connected intelligently to explore environmental information to improve life quality and create a more intelligent world.With the development of economic society and industry, the number of industrial nodes in the industrial internet of things (IIoT) grows at an significant speed.The real-time transmission and exchange of information between these industrial nodes puts forward higher requirements for communication delay and reliability.Under limited time-frequency resources and strict communication quality requirements, in order to ensure ultra-reliable and low-latency communication (URLLC) of massive terminals in IIoT, it is necessary to analyze the existing key problems from the aspects of low delay, reliability, energy efficiency, spectrum efficiency and scalability.In the scenario of IIoT, combined with the characteristics and requirements of URLLC, the key issues of communication in IIoT were studied, including challenges and opportunities in active user detection, random access, resource allocation and convergence of communication and computation.After summarizing and analyzing the key issues and existing technologies, the future research direction was proposed.